YOU and YOUR CREDIT: Credit Dos and Don'ts - Joan P. Elmore; Michael S. Gutter; Travis P. Mountain (EDIS)
This document is FCS7229, part of the YOU and YOUR CREDIT series by Michael S. Gutter, Joan P. Elmore, and Travis P. Mountain. Published by the UF Department of Family Youth and Community Sciences, September 2008.